2000
DOI: 10.1063/1.126052
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent electrical resistance of tin-doped indium oxide on polymer substrates

Abstract: The increase in sheet resistance of indium–tin–oxide (ITO) films on polyethylene terephthalate with increasing tensile strain is reported. The increase in resistance is related to the number of cracks in the conducting layer which depends upon applied strain and film thickness. We propose a simple model that describes the finite but increasing resistance in the cracked ITO layer in terms of a small volume of conducting material within each crack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
373
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 593 publications
(390 citation statements)
references
References 4 publications
5
373
0
Order By: Relevance
“…Weibull statistics on subcritical crack growth in dynamic and static fatigue tests to Eq. (13). The failure probability is obtained from Eq.…”
Section: A Electrical Resistance Increase In Dynamic and Static Fatimentioning
confidence: 99%
See 2 more Smart Citations
“…Weibull statistics on subcritical crack growth in dynamic and static fatigue tests to Eq. (13). The failure probability is obtained from Eq.…”
Section: A Electrical Resistance Increase In Dynamic and Static Fatimentioning
confidence: 99%
“…[5][6][7] As reported in literature, stressinduced cracking is the dominant reason for mechanical failure in barrier layers and subsequent device degradation. The cracking phenomenon is influenced by many factors, such as defect size and location, 5,7-9 internal stress, 10,11 layer thickness, 12,13 and loading type. 11,14 It is important to indicate that crack extension in barrier layers is greatly affected by environmental conditions, due to the fact that the brittle inorganic material is susceptible to environmentally assisted subcritical crack growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional transparent and conductive thin films, such as indium tin oxide (ITO), are brittle. When deposited on flexible substrates, the conductivity of those thin film electrodes tends to deteriorate significantly after subjecting to thermal and/or mechanical strain [1][2][3]. For instance, Na et al [1] found that the resistance of ITO on Polyethylene Terephthalate (PET), increased by ∼40 times after ∼ 2500 bending cycles at a radius of ∼8 mm.…”
mentioning
confidence: 99%
“…The simultaneous measurement of electrical resistance was useful to identify the critical strain for unstable crack growth, related to overall functional failure of the device. It was also used to analyze the interplay between the defect population and the geometry of patterned ITO layers on critical failure [8,9]. A similar approach was used to study the appearance of micro-cracks and related failure mechanisms in thin Cu films on polyimide (PI) substrates [10,11].…”
Section: Introductionmentioning
confidence: 99%